(untitled) (Al-Academy, 2024)
One of the most prominent phenomena in human knowledge is the rapid development in the theoretical and practical fields, and the succession of creative scientific achievements in various fields, which is reflected in the social and cultural life and the mental structure of man. The rapid change witnessed by the present era is nothing but An introduction to a faster and more comprehensive development, the world of the future awaits.